IgY Targeting Bacterial Quorum-Sensing Molecules in Implant-Associated Infections - Dapunt, Ulrike A.; Prior, Birgit; Oelkrug, Christopher; Kretzer, Jan Philippe (Molecules, 2020)
Background: Implant-associated infections are still a major complication in the field of orthopedics. Bacteria can form biofilms on implant surfaces, making them more difficult to detect and treat. Since standard antibiotic therapy is often impaired in biofilm infections, particular interest is directed towards finding treatment alternatives. Biofilm-formation is a well-organized process during which bacteria communicate via quorum-sensing molecules (QSM). The aim of this study was to inhibit bacterial communication by directing avian IgY against specific QSM. Methods: Chicken were immunized against the following QSM: (1) AtlE, a member of the autolysin family which mediates attachment to a surface in Staphylococcus epidermidis; (2) GroEL, the bacterial heat shock protein; (3) PIA (polysaccharide intercellular adhesion), which is essential for cell–cell adhesion in biofilms. Staphylococcus epidermidis biofilms were grown and inhibition of biofilm-formation by IgYs was evaluated. Additionally, human osteoblasts were cultivated and biocompatibility of IgYs was tested. Results: We were able to demonstrate that all IgYs reduced biofilm-formation, also without prior immunization. Therefore, the response was probably not specific with regard to the QSM. Osteoblasts were activated by all IgYs which was demonstrated by microscopy and an increased release of IL-8. Conclusions: In conclusion, avian IgY inhibits biofilm-formation, though the underlying mechanism is not yet clear. However, adverse effects on local tissue cells (osteoblasts) were also observed.
Gesehen am 13.10.2020